The Effects of Work - Life Balance on the Academic employees’ Performance, Motivation and Job Satisfaction among Private and Public Universities of Kurdistan Region - SABIR, ROZHY AZAD; CURA, DR. FATIH (The journal of contemporary issues in business and government, 2021)
The purpose of this study investigates the effects of work - life Balance on the academic employees’ performance, motivation and job satisfaction among private and public universities of Kurdistan Region. Both qualitative and quantitative research methods were used to obtain empirical outcomes. The questionnaires were distributed to the 396 participants among public and private universities in KRG. The results indicate that the employees of the academic world do face challenges of work-life balance in their careers. These challenges are more difficult on the private university employees than the public employees, and the public employees enjoy a fairly better degree of work-life balance than the private universities, even though the rate of the work-life balance culture within the public universities is not at an acceptable level.